"Decent work" in the ready-made garment sector in Bangladesh: The role for ethical human resource management, trade unions and situated moral agency. Issue 1 (8th November 2018) - Khan, Sardana Islam; Bartram, Timothy; Cavanagh, Jillian; Hossain, Md Sajjad; Akter, Silvia
Abstract : Purpose: The purpose of this paper is to examine the perspectives of 26 business owners, managers and supervisors on "decent work" (DW) in the ready-made garment (RMG) sector in Bangladesh. Design/methodology/approach: The qualitative study draws on a framework of ethical human resource management and situated moral agency to establish the ways in which RMG workers are afforded DW. This study uses semi-structured interviews to assess the prospect of DW through applying the ILO's four-pillar framework of DW. Findings: Findings indicate there is a concern among owners and managers of the need to reconcile internal and external pressures to maintain and improve DW. It is evident that ethical practices and moral agency are not self-initiated but in response to mounting political and legal pressures and those of external stakeholders. Employers favour the concept of workers' participation committees as one means to communicate and negotiate with workers rather than recognise trade unions. Research limitations/implications: The research is limited to six organisations in the RMG sector in Bangladesh, but there are implications for all RMG sector organisations to promote reform and DW for all workers. Practical implications: DW necessitates major national and international stakeholders to negotiate and cooperate to ensure the long-term competitiveness and survival of the Bangladeshi RMG sector. Originality/value: The study calls for reform in a developing country where many workers are denied DW.